Role of chest ultrasonography in the prognostic evaluation of patients with community acquired pneumonia: a prospective study - Rennis, Kizhakkepeedika Davis; Anaz, Muhammed; Krishnakumar, Easwaramangalath Venugopal; Thomas, Vadakkan; Robert, Ambooken Poulose (International Journal of Research in Medical Sciences, 2016)
Background: Chest ultrasonography (USG) has shown a growing interest during the last few years in the diagnosis of pneumothorax, pneumonia, or pulmonary contusions. This study was aimed to assess the ability of bedside chest USG in the prognosis of community-acquired pneumonia (CAP) patients and to compare USG with pneumonia severity index (PSI) score and conventional chest radiograph (CXR). Methods: This prospective study was done in patients who get admitted with history and examination findings suggestive of community-acquired pneumonia were included in the study, PSI scoring and CXR were evaluated at the time of presentation. Chest physician performed the thoracic USG. PSI scoring, CXR and USG were repeated on third day and at the time of final outcome. Diagnosis at hospital discharge was taken as the reference standard. Results: Total 100 patients (57±17 years) were included in the study. Correlation between USG, CXR and PSI score were analysed using Spearman's correlation (r). A significant (p = 0.001) correlation between USG and PSI score was found on day 1 (r=0.35), on day 3 (r=0.43) and on the final day (r=0.25). Similarly a significant correlation (p=0.001) was also found between USG and CXR (on day1(r=0.81), on day 3 (r=0.81) and on final day (r=0.74). Conclusions: The chest-ultrasound as a bedside real time, reliable, rapid and non-invasive technique is useful in the prognostic evaluation of pneumonia patients.